Australian Colonial Anglican Bishops and the Eucharist: Broughton, Perry, and Nixon. (25th October 2021) - Douglas, Brian
Abstract: This article examines the eucharistic theology of three colonial Australian Anglican Bishops: Broughton of Sydney, Perry of Melbourne, and Nixon of Tasmania. Examination of their thinking shows that there is a multiformity of view among the three bishops. Broughton engages realism but does this in mainly receptionist manner, seeing Christ as present in the reception of the eucharist and the sacrifice of Christ commemorated and made effective through faithful reception. Perry engages a memorialist view, without realism, and sees the eucharist as a mere remembrance of a past and completed transaction, that is, the death of Christ on the cross. Nixon, under Tractarian influence, expresses a decidedly realist view where Christ is seen to be really present in the elements and a much closer connection is drawn between eucharistic remembrance and Christ's sacrifice. The Oxford Movement is important to all three bishops, with Broughton and Nixon being influenced in a realist direction and Perry using the writings of the Tractarians to argue against realism. The multiformity of view of these bishops explains some of the multiformity of eucharistic theology which continues in the Anglican Church of Australia to this day.